2014
DOI: 10.1371/journal.pone.0094870
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Content and Biochemical Variables of Aloe vera L. under Salt Stress

Abstract: Despite the proven economic importance of Aloe vera, studies of saline stress and its effects on the biochemistry and mineral content in tissues of this plant are scarce. The objective of this study was to grow Aloe under NaCl stress of 0, 30, 60, 90 and 120 mM and compare: (1) proline, total protein, and enzyme phosphoenolpyruvate carboxylase (PEP-case) in chlorenchyma and parenchyma tissues, and (2) ion content (Na, K, Ca, Mg, Cl, Fe, P. N, Zn, B, Mn, and Cu) in roots, stems, leaves and sprouts. Proline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Similar to the previous reports with Aloe Murillo-Amador et al 2014), in the present study, the stressed plants maintained a K/Na ratio significantly lower than those of control plants.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the previous reports with Aloe Murillo-Amador et al 2014), in the present study, the stressed plants maintained a K/Na ratio significantly lower than those of control plants.…”
Section: Discussionsupporting
confidence: 92%
“…Although water use effi cient in Aloe vera during relatively mild water defi cit, plants become stressed at severe water shortage, this species are generally considered most drought and salt-tolerant compared with other Aloe species such as Aloe saponarea (Sun et al, 2003). This salt tolerance in Aloe vera could be related to high calcium and chloride content in their tissues (Ranganathan, 1970) or due to osmotic adjustment caused by the increase in protein, proline and PEP-case activity, as well as the absorption and accumulation of cations under NaCl stress (Murillo-Amador et al, 2014). Other studies have shown that non-halophytic succulent plants with crassulacean acid metabolism such as Aloe vera, shows diurnal variation in acid content and can synthetize more amino acids when they are subjected to mild salt concentration by metabolizing transaminases and inhibiting production of malate dehydrogenase (Karmarkar and Ranganathan, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Murillo-Amador et al (2014) reported that Na and Cl ions accumulated in the cells of roots, stems, leaves and sprouts, thus showing higher Na and Cl contents in sprouts followed by leaves, stems and roots.…”
Section: Abiotic Stresses and Bioactive Moleculesmentioning
confidence: 99%
“…Proline and PEP-case increased as salinity increased in both parenchyma and chlorenchyma of aloe under NaCl stress of 0, 30, 60, 90, and 120 mM, while total protein increased in parenchyma and decreased in chlorenchyma. The increase in protein, proline and PEP-case activity, as well as the absorption and accumulation of cations under moderate NaCl stress caused osmotic adjustment, which kept the plant healthy (Murillo-Amador et al, 2014). …”
Section: Abiotic Stresses and Bioactive Moleculesmentioning
confidence: 99%